Research on Cruise Products Based on the Integration Model of Cruise and Chinese Culture: A Case Study of Adora Magic City - Jiang, Rui; Zhang, Xiaowei (Journal of Social Science and Humanities, 2025)
Taking the Adora Magic City as an example, this paper explores the practical implementation and optimization paths of the “cruise and Chinese culture” integration model. By analyzing the presentation of cultural elements in its spatial design, themed activities, and catering services, the study identifies issues such as superficial cultural integration and insufficient innovation. It is proposed to deepen the integration by excavating traditional culture and leveraging digital technologies for immersive experiences, providing references for the differentiated development of domestic cruise brands.